Analisis Kapasitas Struktur Dinding Squat Wall (Studi Kasus Underpass Pompa Sentiong Jakarta) - Anthony Costa; Bimo Brata Adhitya Bimo; Kencana Verawati Vera (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2021)
There is a potential overflow of a river during rain, resulting in water levels raised beyond normal water levels in the Sentiong Underpass Area, Jakarta in which is one of the strategic locations in Central Jakarta. To guarantee and maximize water flow in the Sentiong Underpass area, a water discharge regulatory system was created to be the form of underground wall structures equipped with pump houses. This wall structure is made of reinforced concrete structures underground at ± 3 m depth. This research aims to evaluate and analyze the underground wall capacity with reference to principles designed by SNI 2847-2013 and SNI 1727-2013. Analysis of data used based on field data including soil test parameters and vehicle traffic. Structural analysis which used is Computer Program (STAADPro), then based on the data obtained from the results of analysis and evaluation can be determined magnitude of displacement and dimensions of the reinforcement. The wall structure in Sentiong Area, Jakarta was planned to use K-300 concrete as high as 3 m underground, 40 cm of wall thickness, bottom floor thickness 40 cm, and upper floor thickness 20 cm. The total length of this underground wall structure was planned 32 m. Based on the results of the analysis, it was found that displacement and capacity structure qualified safely with design steel reinforcement diameters of D13 mm and D16 mm.